Like what? - Tan, Rachel Jiayi (Nanyang Technological University, 2020)
The study comprehensively analyses the interpersonal functions of like, to reflect the attitudes or thoughts of speakers. The subjects of the study were Singaporean Influencers. Their videos that they posted on YouTube, a public video-sharing website were analysed in a multimodal discourse analysis. Like was analysed taking into account its two forms: discourse marker (DM) and quotative like (be+like).